DIFFERENTIATED APPROACH TO SURGICAL TREATMENT OF ACUTE PURULENT PARAPROCTITIS - Bobobekov, A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Improving the results of surgical treatment of patients with acute paraproctitis is an urgent problem of modern emergency proctology. Material. Patients with acute paraproctitis from the Department of Surgical Infection of the Multidisciplinary Clinic of the Tashkent Medical Academy for the period 2000-2022. Results. Radical surgery for acute paraproctitis with an intrasphincter or transsphincter purulent passage passing through the subcutaneous portion of the external sphincter can be performed in one stage with an accurate determination of the purulent course and its internal opening. With a high localization of a pararectal abscess with a purulent course passing through a deep portion of the external sphincter or extrasphincter, it is better to perform a radical operation in the second stage without discharging the patient from the hospital after the elimination of the purulent process in the wound. Conclusion. With extrasphincter and transsphincter purulent passage passing through a deep portion of the external sphincter, the operation of choice is an improved technique using a latex ligature.